2021
DOI: 10.1111/vco.12693
|View full text |Cite
|
Sign up to set email alerts
|

Response‐based modification of CHOP chemotherapy for canine B‐cell lymphoma

Abstract: Despite high initial response rates, a subset of dogs with B‐cell lymphoma responds less robustly to CHOP‐based chemotherapy and experiences shorter survival. One hundred and four dogs with nodal B‐cell lymphoma were treated with a response‐based CHOP (RBCHOP) protocol modified based on response to individual drugs during the first chemotherapy cycle. Dogs achieving complete (CR) or partial response (PR) at week 3, following treatment with vincristine and cyclophosphamide, received RBCHOP 1 (n = 72), a protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In this cohort, continued use of the LOPP protocol was only recommended for those that achieved CR, and a failure to respond to therapy or relapse of disease would necessitate change in protocol or discontinuation of therapy. A failure to respond to chemotherapeutic agents is well reported as a negative prognostic indicator, and this study supports these findings 21,25,47 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this cohort, continued use of the LOPP protocol was only recommended for those that achieved CR, and a failure to respond to therapy or relapse of disease would necessitate change in protocol or discontinuation of therapy. A failure to respond to chemotherapeutic agents is well reported as a negative prognostic indicator, and this study supports these findings 21,25,47 …”
Section: Discussionsupporting
confidence: 86%
“…A failure to respond to chemotherapeutic agents is well reported as a negative prognostic indicator, and this study supports these findings. 21,25,47 Overall, the LOPP protocol used in this study was well tolerated.…”
Section: Discussionmentioning
confidence: 87%
“…Another study reported 121 cases treated by chemotherapy, with a median survival time (MST) of 300 days (range 1–1644 days) [ 50 ]. In yet another study, median RFP was 196 days (range 22–1656 days) and OST was 292 days (range 40–2246 days) of dogs receiving CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) based protocols [ 51 ]. The time of first relapse (RFP) is an accurate indicator of survival statistics because it is not affected by variables influencing OST (such as non-lymphoma related diseases, for instance, accidents, heart disease, infections).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of dogs relapse with resistant lymphoma and median survivals of 10-13 months are reported 5,37 . Although CHOP-based protocols are routinely used for B-and T-cell disease, there is some evidence that more alkylator heavy protocols are more efficacious against T-cell lymphoma however, appropriate randomized trials to test this have yet to be performed [38][39][40] . As responses to chemotherapy for high-grade T cell lymphoma are generally worse than those for high-grade B cell, protocol optimization for T cell disease is ongoing 5 .…”
Section: Treatment and Outcomesmentioning
confidence: 99%